Influence of Colonies’ Morphological Cues on Cellular Uptake Capacity of Nanoparticles - Huang, Siyuan; Su, Qi; Hou, Xiaoqiang; Han, Kuankuan; Ma, Shufang; Xu, Bingshe; Yang, Yingjun (Frontiers in Bioengineering and Biotechnology, 2022)
High transmembrane delivery efficiency of nanoparticles has been attracted substantial interest for biomedical applications. It has been proved that the desired physicochemical properties of nanoparticles were efficient for obtaining the high cellular uptake capacity. On the other hand, biophysical stimuli from in situ microenvironment were also indicated as another essential factor in regulation of cellular uptake capacity. Unfortunately, the influence of colony’s morphology on cellular uptake capacity was rarely analyzed. In this study, micropatterned PDMS stencils containing circular holes with 800/1200 μm in diameter were applied to control colonies’ size. The amino-modified nanoparticles were cocultured with micropatterned colonies to analyze the influence of colonies’ morphology on cellular uptake capacity of nanoparticles. Consequently, more endocytosed nanoparticles in larger colonies were related with bigger dose of nanoparticles within larger area. Additionally, the high cell density decreased the membrane-nanoparticles contacting probability but enhanced clathrin mediate endocytosis. With these contrary effects, the cells with medium cell density or located at peripheral region of micropatterned colonies showed higher cellular uptake capacity of nanoparticles.